Formulasi dan Evaluasi Sediaan Tablet Effervescent dari Ekstrak daun Andaliman (Zanthoxylum acanthophodium Dc.) dengan Variasi Asam dan Basa - Novrika Desclarita Naibaho; Roy Indrianto Bangar; Asyrun Alkhairi Lubis (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Andaliman leaves (Zanthoxylum acanthopodium) are a plant that has the potential to be used as a natural ingredient in the development of herbal preparations. Andaliman leaves are known to contain secondary metabolite compounds, including flavonoids, terpenoids, alkaloids, and tannins. This potential encourages the processing of Andaliman leaves into extracts which are then formulated in the form of effervescent tablets to increase practicality of use. This study aims to produce effervescent tablets of Andaliman leaf extract with good physical quality by making three formulas with varying concentrations of acid-base components. Extraction was carried out using 70% ethanol solvent, then an evaluation of the properties of the resulting granules and tablets was carried out. The test results showed that all formulas met the requirements for organoleptic tests, water content, flow time, and compressibility, but in the angle of repose test only F2 met the criteria. Tablet evaluation showed that all formulas met the organoleptic tests, hardness, friability, and dissolution time, while the uniformity and weight tests still showed discrepancies in some formulas. Overall, formula F2 is the best formula because it meets most of the evaluation parameters for granules and tablets, so it has the greatest potential to be developed as an effervescent tablet preparation from andaliman leaf extract.